PEMANFAATAN MEDIA VIDEO DALAM PEMBELAJARAN ONLINE DI KELAS 3B MI RAUDLATUS SHOLIHIN GEMOLONG SRAGEN TAHUN PELAJARAN 2020/2021 - Sri Hartini; Ratna Widyaningrum; Yulina Amalia Rachmadanti (FKIP, PGSD, Universitas Slamet Riyadi, 2021)
The purpose of this research is:1) Describes the online learning process.2) Analyze the utilization of video media in online learning .3) Knowing obstacles faced by teachers in making videos on online learning .4) Knowing the teacher's strategy in optimizing video media in online learning. in class 3B MI Raudlatus Sholihin Gemolong Sragen Year of Study 2020/2021. The research method used is qualitative descriptive research. Research results: (1) The implementation of online learning includes: a) The Teacher does the planning before carrying out online learning by preparing learning devices in the form of learning videos, RPP, and teaching materials; b) The Teacher conducts the learning process in accordance with the RPP and utilizes the learning video media; c) The teacher conducts a learning evaluation by giving assignments to learners. (2) Teachers utilize video media in carrying out online learning, both homemade videos and videos from youtube. (3) The obstacle in making a learning video is the lack of time in its creation. (4) The necessary strategies: make the video more varied, there need to be workshop activities or seminars I making learning videos